(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The play [cells] and them was created through the process of theatrical devising and performative lectures. It mixes the testimonials of incarcerated women, statistics and reflections about carceral processes and reentry in Brazil, along with an original script about women and social oppression. The play [cells] debuted in 2011 and had many performances until 2015. It was devised anew using experiences provided by the Theatre with Incarcerated Women program, founded in 2019 by Daiane Dordete and Samira Sinara with women of Presídio Regional de Joinville-SC. The project was made possible by Edital de Apoio à Cultura 2016, supported by Sistema de Desenvolvimento pela Cultura of Joinville-SC.